Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

can someone help please:
let f(x)=x^2+x
solve f(x-1)+f(x+1)=6


Sagot :

Step-by-step explanation:

f(x)=x^2+x

so

f(x-1) = (x - 1) ^ 2 + (x - 1)

= x^2 - 2x + 1 + x - 1

= x^2 - 3x

and

f(x+1) = (x + 1) ^ 2 + (x + 1)

= x^2 + 2x + 1 + x + 1

= x^2 + 3x + 2

now

f(x-1) + f(x+1) = 6

x^2 - 3x + x^2 + 3x + 2 = 6

2x^2 = 4

X = √2

brainliest pls took long enough to solve